Optimizing PMI Income and Remittance Management Through Digital Financial Literacy - Sucihatiningsih Dian Wisika Prajanti; Edi Kurniawan; Aji Prasetya Wibawa; Mutiara Kiranawati; Lukluk Ul Muyassaroh (Universitas Negeri Semarang, 2026)
This Community Service program aims to assist PMI in making daily expenditure decisions and financial management for long-term impact. The material presented focuses on how income should be divided according to priorities, how to have a good remittance plan, and how safe digital transactions are carried out. Participants in this service amounted to twenty PMIs. The program included material presentation, discussion, mentoring, and evaluation. Participants conducted a pretest and posttest as a form of measuring participants' understanding after this activity was held. From the results of the quantitative assessment, the average score of participants' understanding of financial literacy increased from the original participant's understanding of financial literacy by 53.7% to 90%. The average N-gain value was 0.79, 16 participants were in a high position and four participants were in the medium category. This shows that financial education is beneficial with the situation faced by PMI.